2002
DOI: 10.1096/fj.01-0711fje
|View full text |Cite
|
Sign up to set email alerts
|

Microarrayed allergen molecules: diagnostic gatekeepers for allergy treatment

Abstract: Type I allergy is an immunoglobulin E (IgE)-mediated hypersensitivity disease affecting more than 25% of the population. Currently, diagnosis of allergy is performed by provocation testing and IgE serology using allergen extracts. This process defines allergen-containing sources but cannot identify the disease-eliciting allergenic molecules. We have applied microarray technology to develop a miniaturized allergy test containing 94 purified allergen molecules that represent the most common allergen sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
250
0
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 407 publications
(261 citation statements)
references
References 87 publications
(26 reference statements)
0
250
0
7
Order By: Relevance
“…2 The 85 allergens on the chip represented 50 allergen families with experimentally confirmed cross-reactivity (see Fig E1 in this article's Online Repository at www.jacionline.org). Sera were collected in 1997 and 2007 from 12 adult allergic patients with confirmed allergy to various airborne and food allergens and from 10 subjects with a negative history of allergy.…”
mentioning
confidence: 91%
“…2 The 85 allergens on the chip represented 50 allergen families with experimentally confirmed cross-reactivity (see Fig E1 in this article's Online Repository at www.jacionline.org). Sera were collected in 1997 and 2007 from 12 adult allergic patients with confirmed allergy to various airborne and food allergens and from 10 subjects with a negative history of allergy.…”
mentioning
confidence: 91%
“…The development of the allergen microarray platform used for preparing the MeDALL allergen-chip has been described earlier [6]. In order to improve the diagnostic spectrum of allergens on the array and to avoid redundant markers, the allergen panel of the current version of ImmunoCAP ISAC (Phadia AB) has been modified by adding more than 70 allergen molecules and by removing cross-reactive allergens which were present in different versions on the chip (Table 1).…”
Section: Design Of the Medall Allergen-chipmentioning
confidence: 99%
“…Allergen microarrays containing large numbers of different allergen molecules have been developed already in 2002 [6] with the goal to allow simultaneous detection of IgE reactivities to a large number of allergen molecules with small serum volumes. These allergen microarrays are comprised of chips containing spotted allergens and were suggested as tools for monitoring the development of allergic sensitization, for the establishment of comprehensive reactivity profiles and to measure eventual changes during the course of disease and various forms of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…An important advan-tage of such a component-resolved immunotherapy (CRIT) approach is the fact that allergic patients can be treated accor ding to their unique reactivity profile (41). In a number of studies, it has been shown that the combination of recombinant allergens with protein microarray technology adds significant benefits to the microarray-based diagnostic approach (16,42): (i) the IgE reactivity profile of individual patients to a large number of allergen components can be obtained reliably in a miniaturized format; (ii) microarray-based IgE testing correlates well with state-of-the-art techniques like ELISA, immunoblot or RAST; (iii) allergen panels can be extended or modified easily to develop popula tion-, region-or disease-specific arrays.…”
Section: Protein Microarrays For the Profiling Of Allergen-specific Amentioning
confidence: 99%
“…multiplex solid-phase immunoassays in a miniaturized form, represent just one of the emerging application in Proteomics (13,14). In principle, protein biochips are the counterparts of DNA biochip technology, using spatially separated and individually addressable microspots of antibo dies (15), proteins (16), small molecules (17) or cell extracts (18) contained in a microarray to monitor the function, interaction or expression of (protein) analytes of interest. Apart from the power of analyzing protein function on the proteome level, the prospect of deve loping diagnostic applications has become an attractive goal for researchers in the protein microarray field.…”
mentioning
confidence: 99%